(untitled) (Al-NASR, 2024)
The article explores the transformative role of Artificial Intelligence (AI) in the legal profession, highlighting its diverse applications and the ethical challenges it raises. AI’s potential to reshape legal systems is examined through its ability to optimize legal research, predict case outcomes, automate compliance, and streamline administrative tasks. The article discusses AI-driven tools like predictive analytics, virtual legal assistants, and smart contracts, all of which improve efficiency and accessibility. It also critically engages with issues such as algorithmic bias, accountability in AI decision-making, data privacy, and the ethical considerations of automating moral judgments. Ultimately, the article emphasizes the need for a balance between AI-driven innovation and the preservation of human judgment, ensuring that AI contributes to a fair, transparent, and equitable justice system.